2010
DOI: 10.1111/igc.0b013e3181e02fe0
|View full text |Cite
|
Sign up to set email alerts
|

Region-Wise Distribution of High-Risk Human Papillomavirus Types in Squamous Cell Carcinomas of the Cervix in India

Abstract: Prophylactic HPV-16/18-L1 vaccines would provide greater than 75% protection against SCC in India. Ranking and frequencies of non-16/18 types were different from earlier reports. Hence, considering the possibility of promotion of persistence of nonvaccine types in the vaccinees due to original antigenic sin and the lack of organized screening programs in India, a broad-based vaccine approach would be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
(16 reference statements)
3
11
0
Order By: Relevance
“…Further observing the increasing trend towards prevalence of different high risk groups other than 16/18 in both Kolkata and Manipur, we also agree according to Pillai et al 2010 that considering the prevalence of other high risk groups circulating among these two groups of population, other than the prophylactic HPV-16/18-L1 vaccine a broad-based vaccine approach would be appropriate for India. At present there are two HPV vaccines under trial in India: Gardasil (Donated by Merck & Co., Inc.) and Cervarix (GlaxoSmithKline).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further observing the increasing trend towards prevalence of different high risk groups other than 16/18 in both Kolkata and Manipur, we also agree according to Pillai et al 2010 that considering the prevalence of other high risk groups circulating among these two groups of population, other than the prophylactic HPV-16/18-L1 vaccine a broad-based vaccine approach would be appropriate for India. At present there are two HPV vaccines under trial in India: Gardasil (Donated by Merck & Co., Inc.) and Cervarix (GlaxoSmithKline).…”
Section: Discussionsupporting
confidence: 82%
“…Another study among the young married women from North India had identified HPV16 as the commonest high-risk type (3%) followed by HPV52 (1.2%) and HPV51 (0.8%) [3]. Recent study from four different regions across India also showed that other than the prevalent HR (High Risk) variant 16 followed by 18 (79.6%), there has also been prevalence of other high risk types (12.4%) such as 45, 73, 31, 56, 52, 58, 59, 33, 68, 51, 35, 26, and 39 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Kolkata, 59–74% of ICC cases are infected with HPV 16 and 2–13.9% cases infected with HPV 18 [7, 18]. Reports from south India showed HPV 16 and HPV18 accounts for 58–69% and 5–19.4% of ICC cases respectively [16, 18].…”
Section: Discussionmentioning
confidence: 99%
“…In Kolkata, 59–74% of ICC cases are infected with HPV 16 and 2–13.9% cases infected with HPV 18 [7, 18]. Reports from south India showed HPV 16 and HPV18 accounts for 58–69% and 5–19.4% of ICC cases respectively [16, 18]. In a similar study from Delhi (north India) reported that HPV 16 and 18 contributing 73.6 and 14.2% cases of cervical carcinoma [19].…”
Section: Discussionmentioning
confidence: 99%
“…The lag period between infection with oncogenic HPV and invasive cervical cancer is 15-20 years [88,89]. In India, the most common (80%) oncogenic types are HPV types 16 and 18; with HPV 16 predominating (80%-90%) [90,91].…”
Section: Hpv Vaccinesmentioning
confidence: 99%